Analisis Menu Dilihat dari Citarasa, Variasi Menu, dan Besar Porsi Makanan yang Disajikan - Nadia Hidayatullah; Irma Eva Yani; Defriani Dwiyanti (Jurnal Sehat Mandiri, 2026)
Poorly managed food organization can affect the quality of the menu served, especially in terms of flavor, variety, and portion size. This study aims to describe the food menu at the Yayasan Bening Nurani (YABNI) Padang Foster Home in 2025 in terms of flavor, menu variety, and portion size. This study used a quantitative approach with a cross sectional design conducted in July-August 2024. The sample consisted of 48 foster children. Data collection was carried out through observation, interviews, questionnaires, and weighing of food ingredients for 7 days. Data were analyzed univariately and presented in frequency distribution and percentage. The results showed that 62.5% of foster children did not like the taste of food and 60.4% rated the appearance of food as unattractive. A total of 54.17% stated that food ingredients and processing were not varied, and 52.08% stated that the color and taste of food did not vary. In addition, the portions of staple foods, animal side dishes, vegetable side dishes, vegetables, and oil are not in accordance with the daily meal recommendations. It can be concluded that the flavors, menu variations, and food portions do not meet the recommended standards. Therefore, it is recommended that institutions improve food management by paying attention to flavor, variety of ingredients and processing, and portions that meet the needs of foster children.